Determination of the boundaries between the domains of stability and instability for the Hill's equation - Grebenikov, E.A.; Prokopenya, A.N. (Нелінійні коливання, 2003)
Stability problem for the Hill’s equation containing two parameters is analyzed with computer algebra system M athematica. The characteristic constant is found as a series expansion in powers of a small parameter e. It has been shown that the domains of instability are located only between the curves a = a(e) on the a−e plane crossing the e = 0 axis at the points a = (2k−1)²/4, k = 1, 2, 3 . . . . The corresponding curves are found as power series in e with accuracy O(e⁶ ). Проблема стабiльностi для рiвняння Хiлла, яке мiстить два параметри, вивчається за допомогою комп’ютерної системи M athematica. Знайдено характеристичну константу в термiнах ряду вiдносно степенiв малого параметра e. Показано, що областi стабiльностi i нестабiльностi знаходяться тiльки на площинi a − e мiж кривими a = a(e), що перетинають вiсь e = 0 в точках a = (2k − 1)²/4, k = 1, 2, 3 . . . . Знайдено вiдповiднi кривi як ряди за степенями e з точнiстю O(e⁶).